Dual-target, real-time PCR for the diagnosis of intraocular Toxoplasma gondii infections. Issue 4 (12th January 2019) - Gomez, Carlos A; Sahoo, Malaya K; Kahn, Ghazala Yasmeen; Zhong, Lina; Montoya, José G; Pinsky, Benjamin A; Doan, Thuy
Abstract : Background: Toxoplasma gondii is the most common infectious cause of posterior uveitis worldwide. Two multicopy targets (B1 and Rep529) are commonly used in T. gondii PCR assays, but studies evaluating these targets in ocular fluid samples are limited. Herein, we determine the analytical characteristics of a single-reaction, internally controlled, dual-target, real-time T. gondii PCR and evaluate the clinical performance of this assay in intraocular fluid samples obtained at a reference ophthalmologic centre in the USA. Methods: Lower limits of detection for the B1 and Rep529 components of the dual-target assay were determined using serial dilutions of cultured T. gondii strain Z185. The dual-target assay was then used to test 148 archived intraocular samples (132 vitreous, 16 aqueous humour) collected at the Francis I. Proctor Foundation between January 2010 and December 2015 for testing by a nested, conventional PCR targeting the B1 gene. Results: The 95% lower limits of detection for the dual-target assay was determined to be 1.05 tachyzoites/mL for B1 and 0.83 tachyzoites/mL for Rep529. Using archived clinical intraocular specimens, the dual-target assay demonstrated 97.2% positive per cent agreement (n=35/36; 95% CI 83.7% to 99.9%) and 99.1% negative per cent agreement (n=111/112; 95% CI 94.4% to 100%) compared with the nested, conventional B1 PCR. Conclusion: This single-reaction, internally controlled, dual-target (B1, Rep529) real-time PCR for the detection of T. gondii DNA in intraocular specimens demonstrated excellent agreement with nested, conventional, B1 PCR. The dual-target design may ensure T. gondii detection when variation is present in one of two target regions.